ALAT PENGGERUS OBAT OTOMATIS BERBASIS MIKROKONTROLER AVR ATMEGA 16 DISERTAI TAMPILAN LCD - Noviana, Eva; Manan, Saiful (Vocational School Diponegoro University, 2012)
Eva Noviana, Saiful Manan, in paper otomatic drug muller based on ATMEGA16 mikrokontroler with LCD monitor explain that in a pharmacy a pharmacist made ​​in accordance with the prescription drugs that have been recommended from the doctor to the patient. The drug is sometimes exist in the form of capsules, so the pharmacist must erode the drug first. Usually the process is still done manually which is less saves time. Because in today's tools - the tools are completely automated. With Automatic Tool muller Drugs Accompanied ATmega16 AVR Microcontroller Based LCD Display is possible to ease the burden on pharmacists, where the application is made up of four series, namely a series of push buttons, ATmega16 AVR microcontroller series, LCD series, muller motor driver circuit. Push button as input in the form of a pushbutton. ATmega16 AVR microcontroller as the central control input and outputan the grinding process medication. LCD ( Liquid Crystal Display ) as output capable of displaying output characters , either letters or numbers. Muller motor driver as government Universal AC to drive the motor. As for writing the program used in this application using C language C language is the software that becomes part of the system which are programs that regulate the working of the microcontroller ATmega16 and overall hardware (hardware ) is connected to the microcontroller ATmega16. Keywords : ATmega16 AVR microcontroller, LCD, muller motor driver.